2009
DOI: 10.1097/iae.0b013e3181a3b848
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Vascular Endothelial Growth Factor in Aqueous Humor of Eyes With Advanced Retinopathy of Prematurity Before and After Intravitreal Injection of Bevacizumab

Abstract: Intravitreal bevacizumab resulted in a marked decrease in the unbound VEGF concentration in eyes with retinopathy of prematurity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 14 publications
0
26
0
2
Order By: Relevance
“…In addition, it is reported that an intravitreal injection of bevacizumab, an anti-VEGF antibody, decreases the intraocular concentration of VEGF, resulting in an improvement of the retinopathy [7]. However, it has not been determined whether additional treatments by PC and/or IVB will be more effective than SB alone.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, it is reported that an intravitreal injection of bevacizumab, an anti-VEGF antibody, decreases the intraocular concentration of VEGF, resulting in an improvement of the retinopathy [7]. However, it has not been determined whether additional treatments by PC and/or IVB will be more effective than SB alone.…”
Section: Introductionmentioning
confidence: 96%
“…The intraocular VEGF level is elevated in diabetic retinopathy, retinal vein occlusion and retinopathy of prematurity [1][2][3][4][5][6][7]. Anti-VEGF drugs are widely used to treat retinal diseases such as age-related macular degeneration (AMD), proliferative diabetic retinopathy (PDR) and macular edema secondary to retinal vein occlusion [8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…After the landmark studies by Aiello and colleagues on the association of retinal neovascularization with the vascular endothelium growth factor (VEGF) in diabetic retinopathy and retinal vein occlusions (Aiello et al 1994(Aiello et al , 1995, consequent investigations showed the associations of VEGF with other neovascular diseases such as exudative AMD and retinopathy of prematurity (Kvanta et al 1996;Matsuoka et al 2004;Nonobe et al 2009;Sato et al 2009). Other studies revealed that besides VEGF, also other cytokines were found in elevated concentrations in the aqueous humour, vitreous and retina of eyes with neovascular disorders.…”
Section: Introductionmentioning
confidence: 99%